Ureolysis-driven sulfidogenic precipitation and pH enhancement for robust bioremediation of zinc-laden acid mine drainage - Cong Peng; Zhenyu Zhang; Zhendong Yang; Li Zeng; Huijun Xi; Zhenghua Liu; Huaqun Yin; Delong Meng; Yonghong Liu; I.A. Ibrahim; Hongjuan Sun; Ke Zhang; et al. (Journal of Environmental Chemical Engineering, 2025)

Preparation and characterization of Ag@MOF-Amomum tsaoko essential oil/waterborne polyurethane composite films for strawberry preservation - Yuyue Qin; Hongda Yu; Haiyan Chen; Yongliang Zhuang; Qiuming Liu; Rui Cui; Cong Zhang; Charles Brennan; Yuanxiang Huang (Food Control, 2025)

Synergistic charge separation and magnetic recovery in a noble-metal-free Fe3O4/TiO2/Bi photocatalyst for bromate reduction - Ying Xu; Shuili Yu; Zhiqiang Fan; Xingli Ji; Cong Huang; Zheng Xu; Rui Liu; Chao Jiang (Journal of Water Process Engineering, 2025)

Bismuth nanospheres enabling sacrificial-agent-free bromate photoreduction and total bromine mitigation for safer water treatment - Ying Xu; Shuili Yu; Zhiqiang Fan; Cong Huang; Lei Li; Rui Liu; Zheng Xu (Journal of Hazardous Materials, 2025)

Adaptive responses and molecular mechanisms of Lactiplantibacillus plantarum to citric acid stress - Han Xie; Wei Zhang; Cong-Rong Shi; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Enhanced moisture tolerance and toluene oxidation activity of δ-MnO2 catalysts by Sn doping: Phase transition and surface protection - Yiming Li; Mengxia Xu; Rui Liu; Shuibo Wang; Taotao Sun; Zijun Yan; Cong Wan; Hongbo Yu; Haocheng Li; Haotian Li; Xudong Zhao; Kaijie Li; et al. (Fuel, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

Subduction-induced crustal growth in the Neoproterozoic continental magmatic arc: Evidence from arc-type high-Mg# diorites and adakitic granitoids in the western Yangtze Block, South China - Rui-Yang Liu; Shao-cong Lai; Yu Zhu; Ren-Zhi Zhu; Min Liu; Jiang-Feng Qin; Fang-yi Zhang; Hang Yang (Precambrian Research, 2025)

Development of a new onset of film boiling model within the fouling layer - Xiaowen Wang; Maolong Liu; Rui Zhang; Tenglong Cong; Yao Xiao; Hanyang Gu (Annals of Nuclear Energy, 2025)

Adaptive neofunctionalization of ancestral CYP6SN2vB following duplication contributes to abamectin resistance in Chilo suppressalis Walker - Shuai Wang; Yuan Xie; Chong Liu; Jin-Wei Liu; Fang-Rui Guo; Song-Tao Qiao; Yu-Ji Xing; Shun-Fan Wu; Chris Bass; Cong-Fen Gao (Insect Biochemistry and Molecular Biology, 2025)

Identification and bioactivity evaluation of ring-opening and lactone forms of enterolactone from sheep fed flaxseed cake - Cong-Cong Zhuang; Chun-Rui Liu; Hai-Yan Xu; Xin-Yue Yang; Dan-Dan Wu; Zhong Zheng; Li-Wei Wang; Zheng Liu; Chao-Mei Ma (Natural Product Research, 2025)

Mass deposition of microbes from wildfire smoke to the sea surface microlayer - Siyao Yue; Yafang Cheng; Lishan Zheng; Senchao Lai; Shan Wang; Tianli Song; Linjie Li; Ping Li; Jialei Zhu; Meng Li; Lianfang Wei; Chaoqun Ma; et al. (Limnology and Oceanography, 2025)
Microbes in the sea surface microlayer (SML) are key to connecting the ocean and the atmosphere, affecting the exchange of matter, momentum, and heat at the interface. However, their sources have never been quantified systematically. Seawater has long been deemed their major source, whereas atmospheric deposition is regarded as trivial or merely providing additional nutrients. Here, combining atmospheric observations and quantitative budget analyses, we show that during the Indonesian peatland wildfire events the smoke can directly deposit abundant microbes into the SML, which can be comparable to the estimated supply from seawater and potentially diversify the microbial community of the SML. This land–air–ocean interaction is relevant for global climate, as it may induce previously unknown effects on the air–sea interactions, especially in an increasingly warming future with more intensifying wildfires.

Ecological security and structural optimization of land space in the Pearl River Delta Urban Agglomeration: an approach based on the footprint family - Cong Huang; Jun Liu; Hanyu Yin; Zhonghao Zhang; Wei Cao; Wenfang Tan; Xufeng Fei; Chen Xu; Lumeng Liu; Jiali Chen; Kai Li; Rui Xiao (Environment, Development and Sustainability, 2025)

CYP321F3 mediates metabolic resistance to methoxyfenozide in rice stem borer, Chilo suppressalis - Fang-Rui Guo; Shu-Chao Wang; Yan Liu; Shuai Wang; Jing-Mei Huang; Hao Sun; Lin-Feng He; Yuan Xie; Song-Tao Qiao; Feng-Xia Yang; Chris Bass; Cong-Fen Gao; et al. (Pesticide Biochemistry and Physiology, 2025)

Research on Characteristics of the Hermite–Gaussian Correlated Vortex Beam - Rui Cong; Dajun Liu; Yan Yin; Haiyang Zhong; Yaochuan Wang; Guiqiu Wang (Journal of Marine Science and Engineering, 2025)
In this work, a new beam named the Hermite–Gaussian correlated vortex beam (HGCVB) is introduced. The intensity and coherence of this HGCVB in oceanic turbulence are analyzed. The results show that the HGCVB displays a splitting property during propagation, and the HGCVB can evolve into the array profile with hollow center beamlets. The results display that the evolution of the intensity of the HGCVB is manipulated by the coherence length δ0 and topological charge M. Meanwhile, the array distribution of coherence of the HGCVB in oceanic turbulence can evolve into a one-spot pattern on propagation. The results show that this HGCVB evolves from a Gaussian beam into a beam array composed of beamlets with hollow centers and may have a potential application in oceanic turbulence.

Heavy metal and metalloid source identification in lake and river sediment in the Honghu Watershed: Coupling land use analysis with RDA and PMF in central China - Yuanzheng Liu; Xiaoguo Chen; Xi Liu; Cong Wang; Lu Zhang; Rui Zhou; Zhi Wang; Xiaolong Huang (Journal of Soils and Sediments, 2025)

Analytical solutions of two-liner tunnels constructed in time-dependent plastic rocks considering loading-unloading stress paths - Hua-ning Wang; Qian Liu; Fei Song; Rui-cong Fu; Ming-jing Jiang (International Journal of Rock Mechanics and Mining Sciences, 2025)

Cis-regulation of the CYP6CS1 gene and its role in mediating cross-resistance in a pymetrozine-resistant strain of Nilaparvata lugens - Pin-Xuan Lin; Yu-Xuan Peng; Ji-Yang Xing; Zhao-Yu Liu; Fang-Rui Guo; Joshua A. Thia; Cong-Fen Gao; Shun-Fan Wu (Insect Biochemistry and Molecular Biology, 2025)

A targeted reformulation of safflower oil: Enhancing anti-inflammatory potential and market competitiveness through ω3 enrichment - Rubab Arshad; Jiawei Wan; Tingyang Ai; Cong Yin; Yonghua Qin; Rui Qin; Jiao Liu; Hong Liu (Food Research International, 2025)